Circulating T cells to infliximab are detectable mainly in treated patients developing anti‐drug antibodies and hypersensitivity reactions. (26th October 2016) - Vultaggio, A.; Petroni, G.; Pratesi, S.; Nencini, F.; Cammelli, D.; Milla, M.; Prignano, F.; Annese, V.; Romagnani, S.; Maggi, E.; Matucci, A.; ,
Summary: Antibodies recognizing infliximab (IFX) may develop in a proportion of treated patients, leading to loss of response or hypersensitivity reactions (HRs). T cell response to IFX has been poorly investigated. This paper was addressed to detect IFX‐specific T cells in treated patients with inflammatory diseases developing, or not, anti‐drug antibodies (ADA) and to correlate the presence of specific T cells with the clinical outcomes of the treatment. A co‐culture system of IFX‐loaded dendritic cells and purified autologous CD4 + T cells was used to detect memory T cells in 32 ADA + and 39 ADA – IFX‐treated patients and control groups. The cytokine profile of IFX‐specific T cells was also studied in culture supernatants. IFX‐specific cell proliferation was detected mainly in cells from ADA + patients, irrespective of their different diseases. HR patients displayed higher T cell proliferation than non‐responder and tolerant patients. A mixed [interferon (IFN)‐γ, interleukin (IL)‐13, IL‐10] cytokine profile was shown in cells from ADA + patients, while IL‐10 was the most frequently detected cytokine in the supernatants of cultures from ADA‐ patients. Immunoglobulin (Ig)E + ADA + patients with previous HRs exhibited a more pronounced type 2 profile than IgE – ADA + patients. This work provides evidence that IFX‐specific circulating T cells are detectable mainly in ADA + patients with HRs, regardless of their disease. The IFX‐induced cytokine pattern partially correlates with the ADA isotype. Abstract : T cell response to IFX is detectable in a proportion of treated patients, mainly in ADA+ patients who displayed an immediate hypersensitivity reaction The cytokine profile partially correlates with the clinical outcome of the treatment Proliferation assay combined with cyokines evaluation may work better than the single test in evaluating cell sensitization